Estrus and pregnancy rate of Simmental-Ongole Crossbred and Ongole Grade heifer after being synchronized and inseminated - Sutiyono, S.; Samsudewa, D.; Suryawijaya, A. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The aim of the study was to examine the synchronization of estrus and artificial insemination in heifers of Ongole grade and Simental-Ongole grade. The research used 19 Ongole Grade (OG) and 18 Simental-Ongole Crossbred (SOC) heifers. This research applied purposive sampling to determine the research population. The criteria to select the population were heifers which have in mature body. The normality of heifer’s reproductive organs were identified by performing rectal palpation, then 50 mg of medroxy progesterone acetate on vaginal sponge was used to synchronized estrus. The estrus heifer was inseminated using frozen semen. The observed parameters were the number of heifers with normal and abnormal reproductive organs, estrus sign and pregnancy. Data were analyzed descriptively. This study showed that OG and SOC with abnormal reproductive organs was 1 heifer (5.56%) and 7 heifers (36.84%), respectively. The responses of estrus synchronization in heifers with normal and abnormal reproductive organs were 94.17% and 100% in OG, and 100% and 42.86% in SOC. Meanwhile, the pregnancy rate was 70.59 and 0% in OG, and 50.00 and 0% in SOC. In conclusion, the number of SOC heifers with abnormal reproductive organs is higher than OG. Estrus synchronization using 50 mg medroxy progesterone acetate increase the amount of estrus and pregnancy in heifers with normal reproductive organs.